A novel hirudin derivative inhibiting thrombin without bleeding for subcutaneous injection - Zhao, Bing; Zhang, Yanling; Huang, Yinong; Yu, Jinchao; Li, Yaran; Wang, Qi; Ma, Yixin; Song, Hou-Yan; Yu, Min; Mo, Wei (Thrombosis and Haemostasis, 2017)
Currently, anticoagulants would be used to prevent thrombosis. Thrombin is an effector enzyme for haemostasis and thrombosis. We designed a direct thrombin inhibitor peptide (DTIP) using molecular simulation and homology modelling and demonstrated that the C-terminus of DTIP interacts with exosite I, and N-terminus with the activity site of thrombin, respectively. DTIP interfered with thrombin-mediated coagulation in human, rat and mouse plasma (n=10 per group) and blocked clotting in human whole blood in vitro. When administered subcutaneously, DTIP showed potent and dose-dependent extension of aPTT, PT, TT and CT in rats (n=10 per group). The antithrombotic dose of DTIP induced significantly less bleeding than bivalirudin determined by transecting distal tail assay in rats. Furthermore, DTIP reached peak blood concentration in 0.5–1 hour and did not cause increased bleeding after five days of dosing compared to dabigatran etexilate. The antithrombotic effect of DTIP was evaluated in mice using lethal pulmonary thromboembolism model and FeCl3-induced mesenteric arteriole thrombus model. DTIP (1.0 mg/kg, sc) prevented deep venous thrombosis and increased the survival rate associated with pulmonary thromboembolism from 30 % to 80 %. Intravital microscopy showed that DTIP (1.0 mg/kg, sc) decelerated mesenteric arteriole thrombosis caused by FeCl3 injury. These data establish that DTIP is a novel antithrombotic agent that could be used to prevent thrombosis without conferring an increased bleeding risk.Supplementary Material to this article is available at www.thrombosis-online.com.
Keywords: Thrombin; r-RGD-hirudin; thrombosis; subcutaneous injection; direct thrombin inhibitor peptide (DTIP)